2015
DOI: 10.1007/s12035-015-9302-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect Comparison of Both Iron Chelators on Outcomes, Iron Deposit, and Iron Transporters After Intracerebral Hemorrhage in Rats

Abstract: Iron overload plays a key role in brain injury after intracerebral hemorrhage (ICH). We explored the roles of ferric iron chelator-deferiprone (DFP)-and ferrous iron chelator-clioquinol (CQ)-in ICH rats through the outcomes, iron deposits, reactive oxygen species (ROS), brain water content, and related iron transporters. One hundred eight Sprague-Dawley rats received intra-striatal infusions of 0.5 U of type IV collagenase to establish ICH models. The rats were randomly assigned to the sham, vehicle, DFP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
6
39
0
Order By: Relevance
“…In a rat model of ICH, CQ administration ameliorated motor dysfunction due to its ability to reduce ROS production in oligodendrocytes 214. In addition, CQ improved neurological outcome, reduced brain oedema and improved mortality rates in a different rat model while enhancing expression of the iron exporting protein FP1 96. These findings suggest CQ as a promising upcoming treatment option for ICH.…”
Section: Treatmentsmentioning
confidence: 84%
See 2 more Smart Citations
“…In a rat model of ICH, CQ administration ameliorated motor dysfunction due to its ability to reduce ROS production in oligodendrocytes 214. In addition, CQ improved neurological outcome, reduced brain oedema and improved mortality rates in a different rat model while enhancing expression of the iron exporting protein FP1 96. These findings suggest CQ as a promising upcoming treatment option for ICH.…”
Section: Treatmentsmentioning
confidence: 84%
“…There has been no research to assess whether it could play an equivalent role in the brain. Nevertheless, iron overload has been shown to increase brain water content following ICH 96. Important to the formation of cerebral oedema is aquaporin 4 (AQP4), one of the most abundant water channel proteins in the brain 97–99.…”
Section: Intracerebral Haemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…However, others claim that although deferoxamine can reduce iron content in the brain, it cannot attenuate injury or improve neurologic function [144146]. In one recent study, ferrous iron chelator (clioquinol), but not ferric iron chelator (deferiprone), improved brain outcomes after ICH [147]. Ferric iron chelator is more likely to facilitate the Fenton reaction process and increase free radical production.…”
Section: Microgliamentioning
confidence: 99%
“…In animal models, heme diffused rapidly through perivascular spaces and induced heme oxygenase-1 enzyme that led to accumulation of ferritin and hemosiderin; generation of free radicals; neuronal injury; and BBB disruption (61). In a rat study, ferrous iron was found to cause brain injury, making this a potential target for chelation therapy (62). Lipocalin-2, a siderophore-binding protein, present in astrocytes, microglia, neurons, and endothelial cells, is involved in cellular iron transport and neuroinflammation.…”
Section: Perihemorrhagic Edemamentioning
confidence: 99%